CTNI-23. IDH1/2wt ANAPLASTIC GLIOMAS OF THE EORTC RANDOMIZED PHASE III INTERGROUP CATNON TRIAL: OVERALL SURVIVAL RELATED TO TREATMENT, MGMT STATUS AND MOLECULAR FEATURES OF GLIOBLASTOMA. (9th November 2020) - Tesileanu, C Mircea S; French, Pim; Erridge, Sarah; Vogelbaum, Michael; Nowak, Anna; Sanson, Marc; Brandes, Alba; Wick, Wolfgang; Clement, Paul; Baurain, Jean; Mason, Warren; Wheeler, Helen; et al.
Abstract: BACKGROUND: The phase III CATNON trial randomized 751 adult patients with newly diagnosed 1p/19q non-codeleted anaplastic glioma to 59.4 Gy radiotherapy +/- concurrent and/or adjuvant TMZ. Here, we present the molecular analysis of the IDH1/2wt subgroup, and associations between molecular characteristics and patient outcomes. METHODS: CNV data and MGMT promoter methylation status were assessed from EPIC methylation array data. IDH1/2 and H3F3A mutation status were determined with a glioma tailored next-generation sequencing panel and TERT promoter mutation status using a SNaPshot assay. Overall survival (OS) was measured from date of randomization. RESULTS: Of 654 assessed tumors, 211 (32%) were IDH1/2wt . An H3F3A mutation was present in 14 tumors ( K27M : n=10; G34R : n=4). Of the remaining 197 patients, 154 tumors had molecular features of glioblastoma according to cIMPACT-NOW 3 criteria (' IDH1/2wt astrocytomas WHO IV'), 39 tumors did not (' IDH1/2wt astrocytomas WHO III'), and 4 had inconclusive molecular data. IDH1/2wt astrocytomas WHO III patients had significantly better survival than WHO IV patients: median OS of 2.83 yrs vs 1.43 yrs respectively [log-rank test: p< 0.001]. Of the 154 IDH1/2wt astrocytoma WHO IV, 55 (36%) were found MGMT promoter methylated. MGMT promoter methylation was prognostic in IDH1/2wt astrocytomas WHO IV patients, with a median OS of 1.86 yrs for methylated vs 1.34 yrs for unmethylated [HR 1.62, p=0.006]. In the IDH1/2wt astrocytomas WHO IV, no effect of concurrent and/or adjuvant TMZ was observed; the HR for OS after RT with any TMZ vs RT alone was 1.31 [95% CI 0.73–2.36, p=0.4] for MGMT promoter methylated and 0.90 [95% CI 0.55–1.45, p=0.7] for unmethylated glioma patients. CONCLUSIONS: Our study validated the prognostic value of the cIMPACT-NOW 3 criteria. MGMT promoter methylation is prognostic but not predictive for outcome to TMZ treatment in this cohort of IDH1/2wt anaplastic gliomas with molecular features of glioblastoma.